Level of corporate social responsibility disclosure of shariah PLCs in Malaysia - Aziz, Muhamad Fikri; Haron, Razali (GBSE, 2021)
Corporate social responsibility disclosure (CSRD) has emerged as a critical issue, with an increasing number of studies being conducted in both developed and developing countries. Accordingly, this study aims to examine the level of CSRD of Shariah PLCs in Malaysia. 175 Shariah PLCs listed on Bursa Malaysia's Main Market from year 2007 to 2017 were chosen as a sample. The level of disclosure is measured using newly developed content analysis. The results show that the level of CSRD of Shariah PLCs in Malaysia is increasing but still at a low level. The "community" theme is the most CSR items disclosed, while "workplace" theme is the least CSR item disclosed in the annual report. There is a need for more encouragement from the Malaysian government or regulatory bodies to encourage all PLCs to report their CSR activities in the annual report.